THE IMPACT OF VIRAL MARKETING USING SOCIAL MEDIA PLATFORMS ON BRAND AWARENESS (CASE STUDY: LANEIGE COSMETIC) - Barri, Hillary Gabriella; Saerang, David P.E; Tumiwa, Johan R. (Universitas Sam Ratulangi, 2017)
Abstract: As the development of technology in this modern era, social media is used by companies as a medium to promote and introduce their products and services to consumers, and also impacts to build their brand. Then the phenomenon of viral marketing is become increasingly popular as part of today's marketing strategy. The purpose of this study was to determine the impact of viral marketing using social media platforms on brand awareness of cosmetic brand from South Korea, Laneige. Social media that represent each social media platform are Facebook, Youtube and Instagram. The data in this study were obtained from questionnaire that distributed to 100 respondents by using purposive sampling method, where the data is further processed by multiple linear regression method. From the analysis results show that viral marketing through these three social media simultaneously gives a significant influence in building brand awareness of 51.5%, but individually only Instagram shows a greater positive effect on brand awareness than the other two variables. Keywords: viral marketing, social media, brand awareness, platform